THE EFFECT OF PRODUCT QUALITY, PRODUCT VARIATION AND PROMOTION TOWARDS THE PURCHASE DECISION OF VIVA COSMETICS - Rustianah; Surya Bintarti; Primaraga Sumantri Indra Wicaksana; Rita Sari (SEAN Institute, 2022)
This study aims to determine the influence of product quality, product variations and promotional activities on the purchasing decision of Viva Cosmetics. This research was conducted using a quantitative descriptive method, the variables in this study were 3 free variables (X) namely the influence of product quality, product variation and promotional activities and bound variables (Y) namely purchasing decisions measured using primary data from questionnaires. The population in this study were consumers who would buy and use Viva cosmetics by calculating samples using a nonpropablity sampling method with an accidental sampling technique consisting of 100 respondents. The data analysis techniques used are validity test, reliability test, multiple linear analysis and t test using the SmartPLS3.3.3 program. The results showed that there was a positive and significant influence of product quality on the purchasing decision of Viva Cosmetics with a value of 38% (0.380). There was a positive and significant effect of product variation on purchasing decisions at Viva Cosmetics with a value of 48.2% (0.482). The promotion has no effect on purchasing decisions Viva Cosmetics by 9.3% (-0.093).